Tourism Family Firm and Generation: Are First-Generation Firms More Conservative? - Clemente-Almendros, José Antonio; Forés, Beatriz; Camisón-Haba, Sergio (European Journal of Family Business, 2024)
By applying the matching technique to a sample of Spanish tourism family firms, we analyze the factors that describe the competitive strategy, asset and ownership structure, and managerial practices of first-generation family firms compared to subsequent generations. Moreover, we employ panel data methodology with the matching procedures to control the individual heterogeneity of family firms, in order to explore debt financing decisions and the particular effect of the controlling generation. The results of the study provide evidence that first-generation firms adopt more defensive strategic positioning based on efficiency and cost control, a smaller endowment of intangible assets, and less of an emphasis on professionalization and human resource management practices. The results also confirm that first-generation firms rely less on debt and adopt a more conservative capital structure.